Reputação corporativa e seus construtos formativos: implicações para a gestão e vantagem competitiva - Thomaz, Jose Carlos (2006)
Corporate reputation has been considered as a resource that can represent a source of value for corporations, given the resources based view perspective. How to define and how to characterize corporate reputation have deserved attention from several authors throughout the last years. It s measurement hasn t been reaching a common-sense and the attributes that have been used for measuring are not always straightforward and useful to the managerial head of corporations in the light of managing this valuable resource. The proposal of this study was to define corporate reputation and to understand how it is built and further study its relation to the performance of corporations. Through theory revision it was decided to use the concept definition based on the theoretical approach of social expectation that uses formative indicators for its measurement. This choice is based, among other reasons, on the possibility to more directly manage variables that represent the concept and hence assist with the achievement of performance derived from reputation, as it is pointed out on the theory of strategy and finance, among others. The development of the study went through a deciding phase, when a scale for construct measuring was created that would fit to the Brazilian cultural reality. Previous research from the author showed that scales developed in other countries present difficulties for the interviewed understanding. Further, these scales present indicators that are distant from the Brazilian sociocultural reality. For this, the following methods where used: systematic revision of the literature, research of qualitative data in four focal groups, field surveys involving 3 successive samples with 379 subjects, and statistics treatment of data collected by the field survey. The second step of the study counted with 1,025 answers from employees from 12 surveyed companies and counted with 1,114 answers from clients from these companies. The surveyed companies are the food companies, the automobile assembler companies, hospitals, colleges and passenger airliner. Data was statistically treated by using the software SPSS. With this software factorial and correlation analysis were performed. Data was also treated by applying structural equations modeling techniques under the method of the partial least squared (PLS), as formative indicators have been used. For this latter treatment the software SmartPLS was used. In this phase of the study an adequate structural model built on formative indicators was obtained. It is concluded that the developed scale is a feasible alternative to the currently available scale. Further, its advantage is that it is built on formative indicators of the corporate reputation. These formative indicators are useful for the managerial head, as they indicate the strategic points of their actuation for construction and maintenance of the corporate reputation. It could be concluded that corporate communication and organizational identification are critical factors for the formation of corporate reputation. It could be also concluded that corporate reputation is a resource, which the corporate performance can take advantage from.